Leadership doesn't have to be lonely: Creating cross-institutional community - Jerry Schnepp; Lisa K. Hanasono; W. John Koolage; Mary-Jon Ludy; M. Elise Radina; Jolie A. Sheffer (Academic Chairpersons Conference Proceedings, 2023)
Presenters and participants will build communities of support through engaging in interactive co-writing surrounding shared challenges, opportunities, and solutions for academic administrators as servant leaders.
Keywords: Collaboration; co-writing; faculty; administrators; leadership; academic culture